Development of Discriminant Model for Classifying Throwers on the Basis of Anthropometric and Physical Fitness Variables - Patidar, Upendra; Saxena, Vikas (Journal for Research in Applied Sciences and Biotechnology, 2023)
The purpose of this study was to develop a discriminate model to classify throwers (discus, javelin and hammer) on the basis of anthropometric variables and to predict their group membership based on the developed model. There were 25 discus throwers, 25 hammer throwers and 25 javelin throwers of age group 17-25 selected as subjects. The data were collected on anthropometric variables i.e. height, weight, sitting height, (leg, arm, hand) length, shoulder width, (chest, hip, thigh, calf) circumference, (back, shoulder, grip and leg explosive) strength. The anthropometric variables were measured by using selected standardized instruments and measuring tapes. Data collected was analyzed at 0.05 level of significance, descriptive statistics and multiple discriminant analysis was applied to classify and predict group membership of the throwers into the discus, hammer and javelin. The results showed that 68.0% of original grouped cases were correctly classified and 45.3% of cross-validated grouped cases correctly classified.